Pengembangan Sistem Informasi Berbasis Web UntukPengarsipan Digital Naskah Lontar (Studi Kasus : Universitas Hindu Indonesia) - I Dewa Agung Dwitya Kania Prabawa; Kadek Oky Sanjaya; I Kadek Andy Asmarajaya (Program Studi Sistem Informasi, Fakultas Teknologi Informasi dan Sains, Universitas Hindu Indonesia, 2026)
The development of information technology has created opportunities in preserving cultural heritage, especially lontar manuscripts with high historical and philosophical value. However, the management of lontar manuscripts at the Hindu University of Indonesia is still conducted manually, leading to risks such as physical damage, data loss, and limited access. This study aimed to develop a web-based information system for digital archiving of lontar manuscripts. The system was developed using the Waterfall method, including requirement analysis, system design, development, testing, and maintenance. The system was implemented using PHP with Laravel 12 framework, Inertia.js, and Vue.js. Testing was conducted using Blackbox Testing and User Acceptance Test (UAT). The results showed that the system improved efficiency in data management and facilitated information retrieval based on categories.